AUTISTIC SPECTRUM DISORDER AND DENTAL MANAGEMENT: SOCIOBEHAVIORAL CHALLENGES AND IMPLICATIONS FOR CLINICAL PRACTICES - Dias Nunes , Lorenna; Lara dos Santos Marques , Késia; Moreira Silva, Poliana; Magno Ribeiro Pinheiro, José; Furtado Ferreira, Rubem; da Silva Rodrigues , Alcimary; Alexandra Fontinelle Pereira, Maria; Campelo Rodrigues, Daniel; Sodré de Oliveira, Fabiana (Revista Gênero e Interdisciplinaridade, 2026)
To analyze the scientific production on the dental management of individuals with Autism Spectrum Disorder (ASD), in light of the current literature, considering its implications for professional practices, health communication, and inclusive care. An integrative review with a descriptive and qualitative approach was conducted in major electronic databases in order to answer the following guiding questions: what are the difficulties and potentialities faced by professionals in the dental management of individuals with ASD? Are professionals adequately trained to provide care for this population? What scientific evidence exists regarding the technologies, behavioral strategies, and resources used in the dental management of patients with ASD? Based on the descriptors employed, 96 articles were identified. After applying the inclusion and exclusion criteria, ten studies were initially selected, and eight were included after full-text analysis. The findings indicate that the dental management of individuals with ASD involves challenges that go beyond technical aspects, encompassing communicational, behavioral, and organizational dimensions of care. The importance of interdisciplinary strategies, professional training, and the use of technologies and educational approaches that promote treatment adherence and the establishment of therapeutic bonds was highlighted. Dental management of individuals with ASD, especially children, is a complex process influenced by cognitive, sensory, and behavioral variations, requiring multiprofessional and interdisciplinary approaches. Limited understanding of these dimensions by professionals may compromise the quality and effectiveness of care. Therefore, further research is recommended to explore communication strategies, behavioral interventions, professional training, family experiences, and the use of assistive technologies, contributing to more inclusive and humanized dental practices.